Fatores que influenciam a permanência de egressos da rede pública no ensino superior: o caso dos estudantes da área de saúde da Universidade Federal da Paraíba - Carvalho, Sandra Maria Cordeiro Rocha de (2019)
Brazilian higher education is detached by strong forms of elitism and selectivity that leave its impressions in the constitution of an excluding, selective and segregating model and it provokes the emergence of the debate of social quotas high education new students‘ access and remaining in public institutions. The thesis study is part of a greater project ―Policies of High Education: the challenges of inclusion, access and remaining in the expansion context of public universities‖, by the general coordination of Prof. Dr. Edineide Jezine, supported by CNPq and carried out with the endorsement of Universidade Federal da Paraíba in collaboration with the National Network of Research Universitas/Br – Sub-Project 5 – Access and Remaining. Its investigative focus is the change of new students socioeconomic profile from the adoption of access expansion policies and compensatory policies or quotas, and make questions about the policies directed to this, as well as the conditions for these high courses permanence. From this reference project, the thesis study has got as an assumption that the factors that influenced the remaining of health students (public school recent graduates that exceeded the selectivity barrier imposed by social and educational inequalities) for the acquisition of academic success are closely bound up to the cultural capital, added to extrinsic factors as social capital and the possession of the economic capital offered during their remaining in this education level. In this context, the thesis study had as objective to analyze the factors that influenced the students inserted by social quotas permanence at UFPB, Campus I, in Health graduation courses, in the perspective of understanding their strategies to obtain success concluding the course of their choice. It was used as a research method the quantiqualitative approach, which investigation was considered from the standpoint of the democratization of the students by social quotas access and permanence, using for analysis the indicators: status, gender, age range and baccalaureate health courses from data provided by STI /UFPB, from 2012 to 2016, the data were analyzed with the SPSS software SPSS, that pointed up a significant concentration of students in this area. About the permanence, the aim was to understand the factors that influenced the social quotas students in nine courses of baccalaureate in health, using as tools a Scale for Evaluation of Students Permanence, validated by Nakamura, Castelo Branco e Jezine (2016). The data were interpreted by the descriptive analysis, with theoretical support in the studies of Bourdieu (1992, 1996, 2003); Nogueira (2009, 2001); Zago (2006,2011); Nakamura, Castelo Branco e Jezine (2016); Mancebo (2008,2010); Prestes e Jezine (2014) among others that contributed for a better analysis about the democratization of access and permanence in a high education public institution. Being the social origin and the economic condition of the student family, with no doubts, the prevailing factors of their permanence in high education, the public policies of access and permanence take on a central role in the inclusion of groups historically excluded, in a trajectory of democratization of Brazilian university.